INOVASI LATIHAN FISIK DALAM MENGURANGI NYERI PUNGGUNG BAWAH DI KELURAHAN KROBOKAN - Mianti Nurrizky; Tunik Saptawati; Silvy Aldila (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Background: Low back pain is a case that is often found in society, this is because people still do not pay attention to proper body posture when carrying out daily activities so as not to cause low back pain. In the Kerobokan sub-district itself, after observation, most of the vulnerable aged 30-60 years had complaints of lower back pain, especially when doing certain activities, such as sitting for too long, lifting gallons, and several other activities. The target and output of this activity are in the form of posters and pocketbooks that will be given to the community so that they can provide benefits. This activity was carried out in the front yard of the Kerobokan Village Hall with the target participants being women farmer groups, PKK, and residents of Kerobokan Village as many as 30 Participants. The results obtained based on the questionnaire showed a significant change in increasing knowledge of lower back pain reduction education before and after the delivery of the material. It can be concluded that knowledge influences the level of society to pay more attention to the right position during activities to prevent lower back pain.